PENDEKATAN TAM DALAM LAYANAN GO-MASSAGE PADA APLIKASI GO-JEK - Widasari, Ni Putu Wulan; Wardana, I Made; Setiawan, Putu Yudi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.03.TAHUN 2018, 2018)
ABSTRACT The meaning of this research wants to explain the effect of perceived ease of use, perceived usefulness, and perceived risk towards attitude and purchase intention of Go-Massage on Go-Jek application. The population of this study is not limited (infinite) which is the user Go-Jek application in Denpasar. The sample in this study was taken with non-probability sampling technique with 120 respondents. The result shows that perceived ease of use and perceived of usefulness have positive and significant effect towards attitude. Furthermore, the results of the study also showed a positive and significant effect of perceived usefulness and attitude towardspurchase intention. Conversely, risk perceptions have a negative and significant effect on attitude and purchase intention. The theoretical implication of this research is that this research reinforces the attitude theory especially the Technology Acceptance Model proposed by Davis (1989). Practical implications are useful for companies to explore the construct which gives significant effect towards purchase intention.  In the future, the company should focus more on perceived usefulness to encourage customer’s purchase intention towards Go-Massage service offered on Go-Jek application Keywords : TAM, Perceived Ease of Use, Perceived Risk, Attitude, and Purchase Intention